Kepemimpinan Kepala Madrasah dalam Berupaya Meningkatkan Moderasi Beragama di MTs Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Andri Saputra (Departement of Mathematics Education, 2024)
Looking at the phenomenon that is currently being widely discussed about the intolerant attitude of a group towards another group. This intolerance is not only intolerant of religion, ethnicity, or other differences, even some occur in the same religion only differing in terms of community organization membership. Therefore, the researcher wants to see the efforts carried out by MTs Hidayatul Mubtadiin Sidoarjo to improve the attitude of religious moderation for its students. Madrasah itself is a place to be used as a center for Islamic religious education, therefore, the researcher wants to know how an educational institution based on Islam provides learning about peace for human life. This study uses a descriptive qualitative research approach. Where the results of this study will explain textually. The purpose of this study is to describe the efforts used by MTs Hidayatul Mubtadiin in improving the attitude of moderation for its students. From this study, the researcher obtained research results that the strategy used by MTs Hidayatul Mubtadiin Sidoarjo is like a strategy in general. Where in the strategy there is planning, implementation, and results. Not only that, researchers also found supporting and inhibiting factors of this program, where the supporting factors are, with few differences between students, it is easier for teachers to explain and also implement. Then the weakness is, the difficulty of teachers in providing real examples of cases of religious moderation.